2010
DOI: 10.1021/pr901188e
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabolic Phenotyping Differentiates Children with Autism from Their Unaffected Siblings and Age-Matched Controls

Abstract: Autism is an early-onset developmental disorder with a severe life-long impact on behavior and social functioning that has associated metabolic abnormalities. The urinary metabolic phenotypes of individuals (age range=3-9 years old) diagnosed with autism using the DSM-IV-TR criteria (n=39; male=35; female=4), together with their non-autistic siblings (n=28; male=14; female=14) and age-matched healthy volunteers (n=34, male=17; female=17) have been characterized for the first time using Additionally, metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
249
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(274 citation statements)
references
References 59 publications
22
249
2
1
Order By: Relevance
“…Furthermore, our observations of elevated plasma taurine and reduced plasma cystine, and in some cases plasma methionine, are consistent with a previous study showing that individuals with ASDs may have a perturbation in sulfur amino acid metabolism. 23 In contrast to our findings, other studies did not identify elevated urinary aspartic acid or reduced urinary cystine 25 or reduction in plasma taurine among their study populations. 24,26 The reason for disparities between these reports is unclear, but may stem from differences in the study populations and the heterogeneity of the ASDs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our observations of elevated plasma taurine and reduced plasma cystine, and in some cases plasma methionine, are consistent with a previous study showing that individuals with ASDs may have a perturbation in sulfur amino acid metabolism. 23 In contrast to our findings, other studies did not identify elevated urinary aspartic acid or reduced urinary cystine 25 or reduction in plasma taurine among their study populations. 24,26 The reason for disparities between these reports is unclear, but may stem from differences in the study populations and the heterogeneity of the ASDs.…”
Section: Discussioncontrasting
confidence: 99%
“…Our current findings are consistent with elevated urinary aspartic acid (11/14; 79%), 22 elevated plasma taurine (7/14; 50%) 22,23 and reduced plasma 24 and urinary 23 cysteine that have been previously reported in children with autism. Furthermore, our observations of elevated plasma taurine and reduced plasma cystine, and in some cases plasma methionine, are consistent with a previous study showing that individuals with ASDs may have a perturbation in sulfur amino acid metabolism.…”
Section: Discussionsupporting
confidence: 92%
“…139 Benzoic acid is a product of protein metabolism by gut microbiota, and altered hippurate level points towards altered metabolism in protein, potentially caused by altered gut microbiota. 140 Another study has reported significant difference in children with autism and normal children in the fatty acid composition of phospholipids, with autistic children having an increased level of most of the saturated fatty acids, except for propionic acid, and a decreased level of polyunsaturated fatty acids. 141 This change in composition of fatty acids can lead to abnormalities in oxidative stress, or cause mitochondrial dysfunction that might play a role in pathogenesis of ASD.…”
Section: Emerging Areasmentioning
confidence: 99%
“…59 Although findings of compositional changes at the species levels are intriguing, siblings. 48 Clearly, more research is needed to clarify the gut microbial dysbiosis and determine the relationship between microbiota and autism.…”
Section: The Association Between Intestinal Microbiome and The Brain-mentioning
confidence: 99%